Inorganic nitrogen absorption in the aquaponics farming of sangkuriang catfish (Clarias gariepinus) at uneven retention periods - Zahidah Zahidah; Yuli Andriani; Yayat Dhahiyat; Isni Nurruhwati; Asep Sahidin; Herman Hamdani; Stephanie Marcelia Victoria (Jurnal Akuakultur Indonesia)
Abstract